Crítica da igualdade jurídica no direito internacional: segurança nuclear e guerra ao terror - Moreira, Júlio da Silveira (2011)
This Master s thesis aims the criticism of legal equality in International Law, since the reference of Marxist criticism in Law Philosophy. Works with the historical and dialectical materialist method, and qualitative research with bibliographic and documentary sources. The starting point are the legal principles of equality, liberty and property, that support the assertion of capitalist society. The criticism of political economy, addressing the characteristics of commodity exchange under capitalism, observe the separation between direct producer and means of production, resulting in the contradictions of the legal principles: legal equality is material inequality, formal liberty is necessity and submission, abstract property is the condition of the dispossessed. Understanding the law from the legal relationships between abstract legal subjects, it criticizes the fetishism of legal rule and the legal ideology. Points to the role of the State as public power for repression and guarantor of legal relations, and especially the State in external relations with other States. The criticism of International Law begins with the study of the works of its founders, Victoria, Grotius and Kant. Then make use of Theory of Imperialism to examine the mechanisms of internationalization of the legal form in the midst of sharing and partition of the world between the capitalist powers. To understand that the internationalization of capitalism is the very negation of its development in the periphery of the system, makes use of the concepts of uneven development, bureaucratic capitalism and break of legality. Reveals the colonial conflict and the civilizational paradigm as inherent to International Law, lasting until the present time, as shown, in theory, the works of Anghie and Miéville, and in factual and concrete plan, the United Nations structure from the binomial peace and collective security and the contradictions in its policy of nuclear security. Finally, the permanence of colonial conflict and civilizational paradigm is evident in State policy called War on Terror, which proposes the revision of concepts of International Law and renew the enemy speech in the stereotype of terrorist, to legitimize imperialist aggressions.